Pemberian Waris Melalui Wasiat Wajibah kepada Anak Angkat Berdasarkan Mazhab di Indonesia - Hayati, Nayla; Laksmi Anindita, Sri (Jurnal Supremasi, 2024)
This article discusses the granting of inheritance to adopted children through mandatory wills based on Islamic law and the distribution of inheritance to adopted children based on various madhhabs in Indonesia. Inheritance is a mandatory right for heirs according to applicable regulations, must meet certain conditions, and must be obtained lawfully. Adopted children can also receive inheritance from their adoptive parents through obligatory wills. However, the distribution of inheritance to adopted children differs. This research addresses two questions: how is inheritance provided to adopted children through obligatory wills according to Islamic law, and how the distribution of inheritance to adopted children in various madhhabs in Indonesia. The research method used is normative juridical with legal and conceptual approaches. The findings indicate that inheritance provision to adopted children through obligatory wills in Islamic law requires the consent of other heirs if it exceeds the predetermined portion, and the distribution of inheritance to adopted children in various madhhabs is not the same as legitimate heirs, namely not more than one-third of the adoptive parent's estate.